ANALISIS PERILAKU MODEL SIR TANPA DAN DENGAN VAKSINASI - Pertiwi, Julia Indah; Putri, Arrival Rince; Efendi, Efendi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Vaccination is one of the methods to control and prevent the spread of infectious diseases. SIR model (susceptible, infected, recovered) without and with vaccination were developed. The behavior of the solutions of the two models is analyzed through stability analysis around the equilibrium points. The stability is also associated with a threshold number indicating the population is free or infected. Analytical results are confirmed with numerical results that are presented on the graphic solution and phase portrait. The results of numerical simulations conclude that vaccination is more effective for inhibiting the transmission of the disease than without vaccination